Sustainability for planetary health: A seventh domain of quality in primary care - Klemenc Ketiš Zalika; Rochfort Andree (Sciendo, 2022)
Climate change is one of the biggest threats to public health. Sustainability is characterized by using resources wisely in a way that protects finite resources and the environment, and takes into account the needs of our planets' inhabitants in the future. Sustainability in health care should be considered as a seventh domain of quality, as it can lead to improvement of patient outcomes, and more capacity for health care workers to engage in quality improvement and thereby improve the quality of care.